"Don't Deny Yourself a Seat at the Table": Supporting the Leadership Development of MSM of Color in HIV Services. Issue 5 (September 2020) - Quinn, Katherine G.; Wolfe, Hester; Vergeront, James
AIDS service organizations have played a vital role in responding to the HIV epidemic, yet many are plagued by an underrepresentation of racial, ethnic, and sexual minorities in leadership positions. In response, the Wisconsin Department of Health Services, HIV Division, created the Wisconsin Health Leaders Fellowship program to provide training and skills to gay and bisexual men of color in HIV service organizations in Milwaukee, Wisconsin. The program was evaluated using in-depth pre- and post-Fellowship interviews with fellows, their agency preceptors, and Fellowship staff ( n = 23 interviews). Results indicate that the Fellowship was successful at developing leadership skills and increasing the confidence of the fellows. However, findings revealed the need to address larger social and structural issues alongside supporting individuals in order to create effective, sustainable change. There is a need for cultural diversity trainings for organizational leaders, changes to organizational hiring and promotion practices, and improving opportunities for formal education for racial and ethnic minority men.